2016
DOI: 10.1136/thoraxjnl-2015-207052
|View full text |Cite
|
Sign up to set email alerts
|

Statin treatment is associated with a decreased risk of active tuberculosis: an analysis of a nationally representative cohort

Abstract: We found that statin therapy was associated with a decreased risk of active TB, and the length of statin therapy affected the TB protection. Given the observational nature of this study, the protective effect against active TB must be confirmed in future randomised trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 44 publications
3
53
0
Order By: Relevance
“…107 As adjunctive therapy in murine TB, statins shorten the time to culture negativity by 1 month, reduce tissue pathology, decrease the proportion of culturepositive relapse cases and enhance bacterial killing. [108][109] Statin usage by newly diagnosed type-2 diabetics did however, not prevent development of TB, 110 and further studies are required.…”
Section: Cholesterol-lowering Drugsmentioning
confidence: 99%
“…107 As adjunctive therapy in murine TB, statins shorten the time to culture negativity by 1 month, reduce tissue pathology, decrease the proportion of culturepositive relapse cases and enhance bacterial killing. [108][109] Statin usage by newly diagnosed type-2 diabetics did however, not prevent development of TB, 110 and further studies are required.…”
Section: Cholesterol-lowering Drugsmentioning
confidence: 99%
“…Treatment with simvastatin in combination with canonical drugs, such as isoniazid, rifampin and pyrazinamide, shortens therapy duration in murine TB 55 . Moreover, a retrospective investigation in a large patient cohort that comprised more than 8,000 new TB cases and 800,000 control patients revealed that there is no risk of TB reactivation upon statin intake 56 . This study was prompted by epidemiological observations that statins improve the clinical outcome of respiratory infections.…”
Section: Tb Chemotherapymentioning
confidence: 99%
“…We have clearly demonstrated that OPN synthesis is effectively inhibited in vitro at less than 1 Statins, which suppress OPN production [27], and their use has been associated with a reduced risk of developing active TB in some studies [28]. Application of the newly-generated compounds to host-directed therapy may be possible.…”
Section: Discussionmentioning
confidence: 88%